Unraveling Quinoa (Chenopodium quinoa Willd.) Defense Against Downy Mildew (Peronospora variabilis): Comparative Molecular Analysis of Resistant “Hualhuas” and Susceptible “Real” Cultivars - Walaa Khalifa; Hala Badr Khalil; Marian Thabet (Plants)
Quinoa (Chenopodium quinoa Willd.) is a new, promising non-conventional useful crop; however, its susceptibility to downy mildew, caused by Peronospora variabilis, is a key obstacle limiting its productivity in Egypt. Identifying and utilizing resistant quinoa cultivars appear to be reliable and cost-efficient strategies for controlling downy mildew, particularly in resource-limited farmers’ fields. This study aimed to evaluate the differential resistance of the Peruvian “Hualhuas” and Bolivian “Real” quinoa cultivars to P. variabilis infection under laboratory conditions to provide precise insight into their basic defense mechanism(s). Inoculated “Hualhuas” plants displayed complete resistance against P. variabilis, with no visible symptoms (incompatible reaction), while those of “Real” plants revealed high susceptibility (compatible reaction), with typical downy mildew lesions on their leaf surfaces. Disease incidence reached about 66% in the inoculated “Real” plants, with most inoculated leaves having lesions of grades 4 and 5 covering up to 90% of their leaf surfaces. Susceptibility indices reached up to 66% in the inoculated “Real” plants. Resistance to P. variabilis observed in the “Hualhuas” plants may have been largely attributed to elevated endogenous H2O2 levels, increased peroxidase (POX) activity and abundance, enhanced phenylalanine ammonia-lyase (PAL) activity and expression, as well as the upregulation of the pathogen-related protein 10 gene (PR-10). The results of this study indicate that the quinoa cultivar “Hualhuas” not only is a promising candidate for sustainable control of quinoa downy mildew but also, through a deep understanding of its molecular resistance mechanisms, would provide a possible route to enhance downy mildew resistance in other genotypes.